2010
DOI: 10.1007/s00011-010-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level

Abstract: FA decreased the hydrogen peroxide-induced IL-1beta, TNF-alpha, MMP-1 and MMP-13 and increased SOX9 gene expression. These findings suggest that FA may prove to be important in the treatment of osteoarthritis. Further research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Thus, the levels of TNF- α and IL-1 β in plasma may reflect the activity of inflammatory cells [25]. A previous report has indicated that FA had the ability to decrease the levels of hydrogen peroxide-induced IL-1 β , TNF- α , MMP-1, and MMP-13, thereby reducing bone destruction [26], synovitis, and the erosion of cartilage in antigen-induced arthritis [27]. Because of their purported protective effects on joints, FA and OD (which contains FA) were administered to CIA rats, and, as shown in Figures 4–10, the animals' symptoms ware ameliorated, the number of inflammatory cells decreased, and the levels of IL-1 β and TNF- α declined by day 28 and day 42.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the levels of TNF- α and IL-1 β in plasma may reflect the activity of inflammatory cells [25]. A previous report has indicated that FA had the ability to decrease the levels of hydrogen peroxide-induced IL-1 β , TNF- α , MMP-1, and MMP-13, thereby reducing bone destruction [26], synovitis, and the erosion of cartilage in antigen-induced arthritis [27]. Because of their purported protective effects on joints, FA and OD (which contains FA) were administered to CIA rats, and, as shown in Figures 4–10, the animals' symptoms ware ameliorated, the number of inflammatory cells decreased, and the levels of IL-1 β and TNF- α declined by day 28 and day 42.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NO can inhibit the synthesis of collagens and proteoglycans and can increase MMP activity in chondrocytes [24]. Pathologic changes include the decreased synthesis of ECM proteins, and the local accumulation of destructive enzymes was observed in H 2 O 2 -stimulated chondrocytes [25]. Drugs for the treatment of degenerative diseases of articular joints may be developed by increasing the synthesis of ECM molecules such as type II collagen and SOX9 and by inhibiting destructive enzymes such as MMPs [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to have anti-inflammation, antiapoptosis, anticancer, and antiaging properties [105, 106]. FA suppressed ROS accumulation in cultured rabbit NP cells and consequently retarded apoptosis.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%